Effect of Solar Radiation and Soil Temperature on the Flow Characteristics in Above Ground and Underground Petroleum Pipelines - Essa, Tabarak M.; Hammadi, Salman H. (Basrah Journal for Engineering Sciences, 2023)
In this proposed study, all environmental factors affecting the aboveground and buried pipes, such as solar radiation and temperature, and soil temperature, have been studied on the characteristics of flow inside the aboveground and underground pipelines by building a mathematical model using MATLAB based on energy balance equations. From the mathematical model, the effect of solar radiation on the aboveground section of the pipeline is significate. During March and an inlet temperature of 34 °C, the pipeline outlet fluid temperature will rise to 50 °C. Other parameters affecting the aboveground section of the pipeline, such as ambient temperature and wind speed, have a much smaller effect on the fluid temperature, and the temperature difference is approximately 4 °C between the highest and lowest pipeline outlet fluid temperature. The result for the underground section of the pipeline showed that the main affecting parameter on the fluid temperature is the burry depth of the pipeline, the deeper the pipeline depth the lower the temperature variation and the lower fluid temperature can be seen, at 1 meter of bury depth the minimum and maximum fluid temperature was 18 °C and 36 °C respectively, and at 5 meters of bury depth, the minimum and maximum fluid temperature was 26 °C and 31 °C respectively. This study also checks different process parameters. Some of these are fluid flow, pipe diameter, and pipe material. The effect of the fluid flow and pipe diameter has a similar impact on the fluid temperature (while fixing all the other parameters), the higher the fluid flow or the smaller the pipe diameter resulted in a better heat transfer and more considerable temperature difference, and vice versa. The final process parameter, pipe material, had little to no effect on the fluid temperature variation.